Red Meat Consumption and Cancer Risk: A Systematic Analysis of Global Data - Hongyue Ma; Xiangming Qi (Foods, 2023)
The association between red meat consumption and cancer risk remains a controversy. In this study, we systematically collected and analyzed global data (from Our World in Data and Global Cancer Observatory) to investigate this association for the first time. Our results confirmed significant positive associations between red meat consumption (RMC) and overall cancer incidence (0.798, p < 0.001), or colorectal cancer incidence (0.625, p < 0.001). Several previously unreported cancer types linked to RMC were also unveiled. Gross domestic product (GDP) per capita were found to have an impact on this association. However, even after controlling it, RMC remained significantly associated with cancer incidence (0.463, p < 0.001; 0.592, p < 0.001). Meanwhile, after controlling GDP per capita, the correlation coefficients between white meat consumption and overall cancer incidence were found to be much lower and insignificant, at 0.089 (p = 0.288) for poultry consumption and at −0.055 (p = 0.514) for seafood and fish consumption. Notably, an interesting comparison was performed between changes of colorectal cancer incidence and RMC in many countries and regions. A lag of 15–20 years was found, implying causality between RMC and cancer risk. Our findings will contribute to the development of more rational meat consumption concept.